Water Hammer Modelling and Simulation by GIS. (2nd August 2012) - Hariri Asli, K.; Haghi, A. K.; Hariri Asli, H.; Sabermaash Eshghi, E.
Abstract : This work defined an Eulerian-based computational model compared with regression of the relationship between the dependent and independent variables for water hammer surge wave in transmission pipeline. The work also mentioned control of Unaccounted-for-Water (UFW) based on the Geography Information System (GIS) for water transmission pipeline. The experimental results of laboratory model and the field test results showed the validity of prediction achieved by computational model.